Sleep Quality as a Mediator of the Relationship Between Cyber Victimization and Depression. Issue 4 (8th June 2020) - Kwon, Misol; Seo, Young S.; Nickerson, Amanda B.; Dickerson, Suzanne S.; Park, Eunhee; Livingston, Jennifer A.
Abstract: Purpose: Cyber victimization is a national mental health concern, especially among adolescents who are digital natives. The current study examined sleep quality as a mediator of the association between cyber victimization and depressive symptoms among adolescents. Design and Method: A prospective study design was utilized with a community sample of adolescents ( N = 801; 57% female; mean age = 14.45, SD = .85) from the eastern United States. Participants completed (a) the Pittsburgh Sleep Quality Index; (b) the Cyber Victimization Scale; and (c) the Center for Epidemiologic Studies Depression Scale Revised via online surveys at baseline and 6‐month follow‐up. The inter‐relationship between variables was analyzed by Hayes' mediation approach. Findings: Cyber victimization was not directly associated with having depressive symptoms 6 months later when controlling for adolescents' poor sleep quality, sex, and age (direct effect [ c '] = .012, t (676) = 1.12, p < .05, confidence interval [CI] ‐.008, .036). The mediation analysis indicated a significant indirect effect of poor sleep quality on the relationship between cyber victimization and depressive symptoms (ab = .005, bootstrapped standard error [ SE ] = .003, bootstrapped CI .001, .011; a is the effect of cyber victimization on poor sleep quality; b is the effect of poor sleep quality on depressive symptoms). Specifically, adolescents' cyber victimization led to poor sleep quality (a = .039, SE = .041, p < .05), which also led to increased depressive symptoms (b = .116, SE = .019, p < .001), after controlling for depressive symptoms at baseline, sex, and age. The indirect effect of cyber victimization on depressive symptoms was estimated through poor sleep quality (a*b = .039(.116) = .0045). Conclusions: The findings suggest that poor sleep quality may be a mechanism through which cyber bullying is related prospectively to depressive symptoms. Interventions for cyber‐victimized adolescents should include assessment of sleep quality and incorporate sleep hygiene education. Clinical Relevance: Adolescents should be screened for cyber victimization and sleep quality. Moreover, promotion of sleep hygiene among cyber‐victimized adolescents may help to reduce depression.